Gastrointestinal Autoimmunity Associated With Loss of Central Tolerance to Enteric α-Defensins - Dobeš, Jan; Neuwirth, Aleš; Dobešová, Martina; Vobořil, Matouš; Balounová, Jana; Ballek, Ondřej; Lebl, Jan; Meloni, Antonella; Krohn, Kai; Kluger, Nicolas; Ranki, Annamari; Filipp, Dominik (Gastroenterology, 2015)
BACKGROUND & AIMS: Autoimmune polyendocrinopathy candidiasis ectodermal dystrophy (APECED) is an autoimmune disorder characterized by chronic mucocutaneous candidiasis, hypoparathyroidism, and adrenal insufficiency, but patients also develop intestinal disorders. APECED is an autosomal recessive disorder caused by mutations in the autoimmune regulator (AIRE, which regulates immune tolerance) that allow self-reactive T cells to enter the periphery. Enteric α-defensins are antimicrobial peptides secreted by Paneth cells. Patients with APECED frequently have gastrointestinal symptoms and seroreactivity against secretory granules of Paneth cells. We investigated whether enteric α-defensins are autoantigens in humans and mice with AIRE deficiency. METHODS: We analyzed clinical data, along with serum and stool samples and available duodenal biopsies from 50 patients with APECED collected from multiple centers in Europe. Samples were assessed for expression of defensins and other molecules by quantitative reverse transcription polymerase chain reaction and flow cytometry; levels of antibodies and other proteins were measured by immunohistochemical and immunoblot analyses. Histologic analyses were performed on biopsy samples. We used Aire(-/-) mice as a model of APECED, and studied the effects of transferring immune cells from these mice to athymic mice. RESULTS: Enteric defensins were detected in extraintestinal tissues of patients with APECED, especially in medullary thymic epithelial cells. Some patients with APECED lacked Paneth cells and were seropositive for defensin-specific autoantibodies; the presence of autoantibodies correlated with frequent diarrhea. Aire(-/-) mice developed defensin-specific T cells. Adoptive transfer of these T cells to athymic mice resulted in T-cell infiltration of the gut, loss of Paneth cells, microbial dysbiosis, and the induction of T-helper 17 cell-mediated autoimmune responses resembling those observed in patients with APECED. CONCLUSIONS: In patients with APECED, loss of AIRE appears to cause an autoimmune response against enteric defensins and loss of Paneth cells. Aire(-/-) mice developed defensin-specific T cells that cause intestinal defects similar to those observed in patients with APECED. These findings provide a mechanism by which loss of AIRE-mediated immune tolerance leads to intestinal disorders in patients with APECED.
Keywords: senioři; T-Lymphocytes; Intestines; mladiství; Polyendocrinopathies, Autoimmune; T-lymfocyty; myši inbrední C57BL; Middle Aged; mužské pohlaví; Mice; Adult; mladý dospělý; Transcription Factors; AIRE Protein; myši knockoutované; dítě; Microbiota; střeva; Child; transkripční faktory; Child, Preschool; DEFA; Young Adult; Mouse Model; autoimunita; ženské pohlaví; protein AIRE; zvířata; Autoimmunity; předškolní dítě; Humans; lidé středního věku; Mice, Knockout; alpha-Defensins; myši; Intestinal Crypt; autoimunitní polyglandulární syndromy; dospělí; alfa-defensiny; Female; Aged; Adolescent; Mice, Inbred C57BL; lidé; Male; Animals